Síntese e caracterização de catalisadores de Pt suportados em Sm2O3-CeO2-Al2O3 aplicados à reações de reforma do metano - Duarte, Renata Bessa (2010)
The effect of the preparation method of the Pt/12Sm2O3-Al2O3 catalysts and the effect of the content of the oxides promoters in the Pt/xSm2O3-yCeO2-Al2O3 catalysts on the properties and catalytic behavior in the reaction of partial oxidation of methane (POM) were investigated. Once performed characterizations of the catalysts promoted by Sm2O3 synthesized by different methods, the most promising method was used to make a study of the content of the oxide promoters of samarium and cerium. Catalysts containing both oxide promoters were most active for this reaction because they have a higher density of Pt sites, according to data obtained from the reaction of dehydrogenation of cyclohexane. With increasing content of Sm2O3 greater stability during the reaction is observed in the catalysts. This stability provided by the samarium oxide support can also be evidenced by measures of N2 physisorption, X-ray diffraction (XRD), temperature programmed reduction (TPR) and thermogravimetric analysis (TGA). XPS results show that the high stability of the catalysts should not be due to the increase in the bond strength of Pt-O-Sm or Pt-O-Ce, which would hinder the diffusion of Pt. Therefore, it is possible that the lack of mobility of the promoted support is responsible for the stability observed.